Depression In Adolecents - Rian Yuliyana (Journal of Health Science and Nursing Study, 2022)
Background: A mental disorder that can be suffered by all is depression. The health burden brought on by depression makes depression an important public health issue. Objective; this study was descriptive survey on depression in adolescents on Berakit village, Riau Islands. Method:  a descriptive design was employed 65 participants by simple random sampling at Berakit Village, Bintan, Riau Island. Depression Anxiety Stress Scale (DASS) were use as the instruments. Data was analyzed by using descriptive statistics. Results of this study found that most mean the range score in screening for depression was normal (83%). Most most mean the range score in screening for anxiety adolescent was early anxiety (22%). Moreover, the most of participant rate middle stress (24%). Conclusion these finding indicated that there are depression cases in further intervention to promote management stress to adolescent in seacoast.   Key words: Depression, anxiety, adolescent